Telemidwifery: Transforming Maternal Health Care in the Digital Era - Hikmah, Hikmah; Aldo, Mutia Perdana Hairun Nisa; Susilawati, Intan Rina (Oshada, 2025)
Telemidwifery represents a digital transformation in maternal health services by integrating information and communication technology into midwifery care. This study aims to analyze the effect of telemidwifery on maternal health service satisfaction in Indonesia using a quantitative approach with a survey of 150 respondents, consisting of pregnant and postpartum mothers who have used telemidwifery applications or online consultation platforms. Data were analyzed using simple linear regression to measure the relationship between the intensity of telemidwifery use and user satisfaction. The results show that telemidwifery has a positive and significant effect on maternal satisfaction (β = 0.486; t = 6.427; p = 0.000; R² = 0.302). This finding indicates that telemidwifery effectively increases accessibility, continuity of care, and user trust in midwifery services. The study also reinforces that digital health innovations play a crucial role in overcoming geographical barriers, especially in rural and remote areas. The implementation of telemidwifery aligns with global health trends toward sustainable, equitable, and technology-driven maternal care. Further development requires strengthening midwives’ digital literacy, integrating telehealth systems into national health policies, and ensuring data privacy and ethical standards.